2010
DOI: 10.1128/aac.01050-10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Antifungal Activity of Terpenoid Phenols Resembles Calcium Stress and Inhibition of the TOR Pathway

Abstract: Terpenoid phenols, including carvacrol, are components of oregano and other plant essential oils that exhibit potent antifungal activity against a wide range of pathogens, including Candida albicans, Staphylococcus aureus, and Pseudomonas aeruginosa. To gain a mechanistic view of the cellular response to terpenoid phenols, we used Saccharomyces cerevisiae as a model organism and monitored temporal changes in metabolic activity, cytosolic and vacuolar pH, and Ca 2؉ transients. Using a panel of related compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(168 citation statements)
references
References 34 publications
6
141
3
5
Order By: Relevance
“…This diversity can either be in regard to presence and absence of certain phytochemicals or be in the levels of concentration of a certain phytochemical in a plant sample. Therefore, the observed activity in the current study could also be attributed to the presence of flavonoids and terpenoids which have been shown to have capacity to traverse the highly hydrophobic tubercle envelop (Edwards and Ericsson, 1999;Rao et al, 2010).…”
Section: Test For Phenols Terpenoids Flavonoids Anthraquinones Alkaloidsmentioning
confidence: 94%
“…This diversity can either be in regard to presence and absence of certain phytochemicals or be in the levels of concentration of a certain phytochemical in a plant sample. Therefore, the observed activity in the current study could also be attributed to the presence of flavonoids and terpenoids which have been shown to have capacity to traverse the highly hydrophobic tubercle envelop (Edwards and Ericsson, 1999;Rao et al, 2010).…”
Section: Test For Phenols Terpenoids Flavonoids Anthraquinones Alkaloidsmentioning
confidence: 94%
“…The provision of terpenoids with high concentration even can cause cellular activities stopped and the cells dead. 15 The results showed that the increasing of the concentration of Citrus Limon essential oil could decrease the number of Candida albicans colonies. In this research, 80% Citrus Limon essential oil expressed the minimum inhibitory power against Candida albicans.…”
Section: Discussionmentioning
confidence: 89%
“…It indicated that presence of terpenoids, steroids, alkaloids are responsible for control the growth of dermatophytic fungal pathogens. Terpenoid phenols, including carvacrol, are components of oregano and other plant essential oils that exhibit potent antifungal activity against a wide range of pathogens [26] . The anti spore germination effect was higher in methanolic extract may be the presence of trepenoids and sterols.…”
Section: Discussionmentioning
confidence: 99%